Comparison of a new ELISA assay with the flow cytometric assay for platelet vasodilator-associated stimulated phosphoprotein (VASP) phosphorylation in whole blood to assess P2Y12 inhibition - Jakubowski, Joseph A.; Bourguet, Nicolas; Boulay-Moine, Danièle; Sugidachi, Atsuhiro; Yamaguchi, Shinji; Barragan, Paul; Zhou, Chunmei; Moulard, Maxime (Thrombosis and Haemostasis, 2012)
Thienopyridines and other agents target the platelet P2Y12 receptor and inhibit several platelet activities mediated by adenosine diphosphate (ADP). The measurement of vasodilator-associated stimulated phosphoprotein (VASP) phosphorylation, expressed as platelet reactivity index (PRI), mirrors the degree of P2Y12 receptor inhibition and can detect the well-known variable response to clopidogrel. The commercially available VASP assay uses flow cytometry (FC) and requires that the test be run within 48 hours of blood collection. A new ELISA VASP assay offers the advantages of using more widely available technology and the potential to freeze and store samples before analysis. The objectives of the present study were to compare the performance of the ELISA and FC methods and to describe the relative flexibility of the ELISA-based assay. Human blood samples encompassing a wide range of levels of P2Y12 blockade achieved in vitro by preincubation with P2Y12 antagonists or in vivo from patients treated with clopidogrel were included, reflecting the wide spread of values reported in clinical studies. The correlation between the PRI measured by ELISA and FC was highly significant (r=0.95, p<0.001), (n=80). After the initial activation, samples were stable for at least four weeks when frozen (−20°C) prior to analysis by ELISA. Frozen samples from patients treated with clopidogrel appeared stable for up to nine weeks. Based on these results, the ELISA-based assay appears to provide a reliable and more flexible alternative to the FC method to determine P2Y12 receptor blockade and may enable more extensive utilisation of the VASP assay in clinical studies.Note: All work done at BioCytex, Marseille, France and Daiichi Sankyo, Tokyo, Japan.
Keywords: VASP; ELISA; flow cytometry; clopidogrel; prasugrel